Viability Of the Extended Technology Acceptance Model: An Empirical Study - Islam, Abu Yousuf Mohammed Atiquil (Universiti Utara Malaysia Press, 2011)
The prime objective of this study is to validate the extended technology acceptance model (ETAM) by incorporating two intrinsic motivation attributes, namely, computer self-efficacy and satisfaction into the original TAM to compare its viability testing on their satisfaction of the wireless internet service at a university. Besides, it evaluates gender invariant of the causal structure of this extended TAM. A total of 285 students from five major faculties (Education, Human Sciences, Engineering, ICT and Economics) were taken as respondents. The questionnaire's reliability and validity were established through a RASCH analysis. The results as analyzed by Structural Equation Modelling (SEM) indicate that students perceived ease of use had a statistically significant effect on their satisfaction. The study revealed that gender did not exert any influence as a moderating variable towards students' satisfaction in using Wireless Internet. The findings contributed to a better understanding of the TAM and technology satisfaction among students.